Identification of Waste in Outsole Production Process Using Waste Assessment Model and 5W 1H Method - Hernanda, Santoso Bayu; Sumiati, Sumiati (Newinera Publisher, 2025)
UD. Santoso is a small and medium industry (IKM) engaged in the production of footwear, especially outsoles. In the production process, UD. Santoso faces various problems that result in waste such as: high percentage of defects, production not in accordance with market forecasts, long machine setup, long distances between rooms, and inefficient movement of materials. The company also realizes that the outsole production process is not efficient and there is a lot of waste. This study aims to identify the type of waste that occurs using the waste assessment model method, as well as provide recommendations for improvement to improve production efficiency with 5W1H analysis. From the results of the analysis, it was found that the three highest types of waste were the main causes, namely: motion (19.34%), which was caused by the distance between the production warehouse and the storage was quite far. Second, over-production (16.90%), caused by over-focusing on machine capacity and inaccurate forecasting. Third, defects (16.79%), caused by incorrect drawing techniques. As a solution, companies are advised to make more effective layouts, set production targets, and provide training in withdrawal techniques.